Atopic dermatitis in children: a cross-sectional study of its impact on quality of life - Babu, Asha; Thomas, Naveen; Zacharias, Rekha; Francis, Johny Vakayil; Patel, Dimple (International Journal of Contemporary Pediatrics, 2024)
Background: Atopic dermatitis, characterized by chronic inflammation of the skin, manifests with symptoms such as itching, skin discomfort, and sleep disturbances, significantly impacting the physical health and daily functioning of affected children. We embarked on this study to assess the Quality of Life of children with AD, identify factors that influence their QoL, and determine the specific domains of QoL most affected by the condition. Methods: Children up to 16 years of age, who met the Hanifin and Rajka’s diagnostic criteria for AD, were identified. The severity of AD was assessed using the severity scoring of atopic dermatitis index, and QoL was assessed using validated questionnaires: the infants dermatitis quality of life index for children under 4 years and the children’s dermatology life quality index for children 4 years and above. Results: A total of 70 children with AD were enrolled in the study. The mean QoL (IDQOL/CDLQI) score for children with AD was 6.7±5.05 and QoL was significantly impaired in children with more severe disease. The domains of QoL most affected by AD were related to pruritus, sleep disturbances, mood changes and treatment related issues. The duration of illness and the presence of other atopic comorbidities showed a significant correlation with QoL impairment, whereas age, gender and socioeconomic status demonstrated no such correlation. Conclusions: This study highlights the substantial impact of AD on the QoL of affected children, especially due to symptoms like itching and sleep disturbances.